‘Access to environmental information – the international perspective and a comparative review of South African and German law in the context of nuclear energy development' - Raddatz, Fabian Sydney (Institute of Marine and Environmental Law, 2026)
At the outline, it should be noted that environmental concerns are essentially subject to public interest, including affected individuals, communities and NGOs. Consequently, the civil society has to get an opportunity to participate in all environmental decision-making on the governmental level to ensure a democratic administrative process2.